2012
DOI: 10.5267/j.msl.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

A social work study on job satisfaction

Abstract: Job satisfaction plays an important role on having sustainable growth in any business units. When an unsatisfied employee leaves, the business unit not only loses an employee but also it loses an intangible asset. Therefore, it is necessary to evaluate overall job satisfaction occasionally and provide some guidelines for improving work conditions. The proposed study of this paper uses five questionnaires, which are associated with job motivation, job satisfaction and organizational commitment. We have selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Moreover, the effect of the work locus of control, as moderator, on the relationship between the staff's wellbeing and their organizational commitment relational and had some necessities. Iravani (2012) explained that job satisfaction could have sustainable growth in any business units. In fact, he explained that when an unsatisfied employee leaves, the business unit not only loses an employee but also it loses an intangible asset.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effect of the work locus of control, as moderator, on the relationship between the staff's wellbeing and their organizational commitment relational and had some necessities. Iravani (2012) explained that job satisfaction could have sustainable growth in any business units. In fact, he explained that when an unsatisfied employee leaves, the business unit not only loses an employee but also it loses an intangible asset.…”
Section: Introductionmentioning
confidence: 99%
“…Iravani (2011), for instance, reported that there were some positive relationships between job satisfaction (Seal & Knight, 1988) and other factors including wage increase, psychological needs, physical equipment, entertainment equipment and work-team. Khorshidifar and Abedia (2011) performed an empirical study on the effect of stress on the relationship between locus of control and job satisfaction and job performance.…”
Section: Introductionmentioning
confidence: 99%